Improvement of survival and development of Pacific white shrimp Litopenaeus vannamei larvae by feeding taurine enriched rotifers - Jusadi, Dedi; Ruchyani, Syarifah; Mokoginta, Ing; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2011)
ABSTRACTThe objective of the present experiment was to study the most optimum taurine enrichment concentration of rotifers in improving Pacific white shrimp larva Litopenaeus vannamei survival and development. White shrimp larvae at sixth naupliar stage were reared in 12 units of 500 L fibre glass tanks with a stocking density of 125 ind/L. Starting from zoea two stage (Z-2), the larva was provided with rotifers with different taurine enrichment concentration according to the treatments, i.e. 0 mg/L enrichment medium (A), 25 mg/L (B), 50 mg/L(C), and 100 mg/L (D). The results show that different taurine concentration in the enrichment media increased taurine level in rotifers. Furthermore, the administration of taurine enriched rotifers up to 50 mg/L significantly improved larval survival and may accelerate larval development. The experimental results also concluded that a concentration of 50 mg/L is the most optimum taurine enrichment concentration of rotifers for the improvement of white shrimp larval survival and developmental stage.Keywords: taurine, rotifer, white shrimp, enrichmentABSTRAKPenelitian ini bertujuan untuk mengkaji konsentrasi optimum taurin melalui pengayaan pada rotifera terhadap tingkat kelangsungan hidup dan perkembangan stadia larva udang vaname Litopenaeus vannamei. Larva udang vaname stadia naupli-6 dipelihara dalam 12 tangki fiberglass volume 500 L dengan kepadatan 125 ind/L. Dimulai sejak stadia zoea 2 (Z-2) larva diberi rotifera yang diperkaya dengan taurin dengan konsentrasi yang berbeda sesuai dengan perlakuan, yaitu 0 mg/L media pengkaya (A), 25 mg/L (B), 50mg/L (C), dan 100mg/L (D). Hasil penelitian menunjukkan pengayaan taurin pada konsentrasi yang berbeda menyebabkan peningkatan kandungan taurin rotifera. Sementara pemberian rotifera yang diperkaya taurin hingga 50 mg/L meningkatkan kelangsungan hidup dan mempercepat perkembangan stadia larva udang. Berdasarkan hasil penelitian ini dapat disimpulkan bahwa pemberian rotifera yang diperkaya taurin dengan konsentrasi 50 mg/L menghasilkan tingkat kelangsungan hidup tertinggi (53,5%) dan perkembangan larva yang tercepat (p<0,05) dibandingkan perlakuan lainnya.Kata kunci: taurin, rotifera, udang vanname, pengayaan